Pious Labor Islam, Artisanship, and Technology in Colonial India - Lanzillo, Amanda (University of California Press, 2024)
In the late nineteenth and early twentieth centuries, working-class people across northern India found themselves negotiating rapid industrial change, emerging technologies, and class hierarchies. In response to these changes, Indian Muslim artisans began publicly asserting the deep relation between their religion and their labor, using the increasingly accessible popular press to redefine Islamic traditions "from below." Centering the stories and experiences of metalsmiths, stonemasons, tailors, press workers, and carpenters, Pious Labor examines colonial-era social and technological changes through the perspectives of the workers themselves. As Amanda Lanzillo shows, the colonial marginalization of these artisans is intimately linked with the continued exclusion of laboring voices today. By drawing on previously unstudied Urdu-language technical manuals and community histories, Lanzillo highlights not only the materiality of artisanal production but also the cultural agency of artisanal producers, filling in a major gap in South Asian history. "The history of technology in South Asia has mostly been devoted to the 'temples of modernity,' accenting the monumental, the secular, and the modern. Amanda Lanzillo introduces us to a very different history, where technology, religion, and tradition domesticate modernity within intimate laboring cultures." - Projit Bihari Mukharji, Professor of History, Ashoka University "Lanzillo explores entirely new vistas of the intertwined history of religion and labor in colonial South Asia, making a fascinating case for the flourishing of an 'artisan Islam' in the industrializing cities of the subcontinent." - Nile Green, Ibn Khaldun Endowed Chair in World History, University of California, Los Angeles "Pious Labor opens up vital new conversations between scholars of Islam, vernacular print culture, labor, and technology studies. This work will have a major impact on the fields of South Asian history, Islamic studies, and beyond." - Julia Stephens, Associate Professor of History, Rutgers University